KONSEP PENGEMBANGAN MODUL PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) BERBASIS INTEGRATED CURRICULUM PAI DENGAN TEMA KEWIRAUSAHAAN - Mariani; Eni Zulaikah; Salamah (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Islamic Religious Education is one of the subjects in the national curriculum which is certainly expected to support the realization of national education goals. One of the visions and missions to realize educational goals is to improve the character of the nation with the Pancasila Student Profile Strengthening Project (P5) is part of the independent curriculum. P5 with theme of entrepreneurship is an educational initiative that aims to introduce the concept entrepreneurship to students while at the same time will provide an impact of Pancasila values to the students. Meanwhile, Islamic Religious Education learning in school is still dichotomous between religious knowledge. The purpose of this study is to determine the concept of developing P5 teaching module based on the integrated curriculum with the Entrepreneurship theme. This study uses a literature review, data is analyzed through books, journals and other research results. Based on the data analysis, the integrated development model is carried out by combining several lessons using one theme, which can be done with the Pancasila Student Profile Strengthening Project (P5) with the entrepreneurship theme. It needs to be supported by subject teachers by collaborating with each other to form a P5 team in order to achieve the results of the Pancasila Students Profile as well as the objectives of the integrated curriculum model.